Fuel Analysis HSD Diesel and Bio Diesel Related Engine Performance Reach Staker Kalmar in PT. Meratusline - Ponidi Ponidi; Ibnu Salam (Universitas Muhammadiyah Sidoarjo, 2019)
Modern diesel engines require low sulfur fuel. So we held some external lab test of solar sampling at some diesel vendor to know its sulfur content. so that obtained by diesel vendor approaching standart. The sulfur content of DirjenMigas (0.25% w / w) is HSD of AKR of 0.153% w / w and Biosolar from ENEOS is 0.0343% w / w. The selection of two types of fuel is based on the needs of fuel by engine manufacturers (OEM) and the most efficient sulfur content. Side effects of excess sulfur content have resulted in the clogging of its fuel pump injection. So that the fuel supply to the combustion chamber is disrupted Too high sulfur levels also cause dangerous emissions and decreases its performance engine. To know the performance of the machine by Dyno / Dinamometer test machine performance, this is as a comparison material where the most efficient fuel that must be selected, to get the best engine performance, by three criteria taken such as Torque, Power engine, and Fuel Consumtion. So obtained Torque Output generated by HSD with Torque Reading result 810 lb.ft@1990 Rpm, Power result 302 HP, and specific fuel consumption 0.02 (kg / PS.jam) if compared with Bio diesel Torque output of 750 lb.ft @ 1960 rpm, Power of 283 HP and Specific fuel consumtion 0.01 (kg / PS.jam). of the data can be taken diesel decision that must be taken according to the level of fuel efficiency and engine performance is HSD solar AKR vendors with the level of efficiency of power output 6.29%, torque 7.40% and specific fuel consumption 50%.